ANALISIS KESALAHAN BAHASA INGGRIS DALAM â€œSTATUSâ€ DI MEDIA SOSIAL FACEBOOK - PODOMI, INKA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACT This research entitled â€œError Analysis of English in Status in the Social Media Facebookâ€, is an attempt to identify, classify, and analyze and describe the kinds of errors in the use of Social Media Facebook.Â This research is expected to help in language development of and give information in order to increase knowledge to understand errors analysis especially in the Facebook. Ellisâ€™s theory is used to identify, classify, and analyze the Error Analysis of English in Status in the Social Media Facebook.Â This research used an error analysis which has been done in several stages preparation was made by reading status in the Facebook. Data was taken from Status in the Facebook. The writer use some techniques of analyzing the data, as follows, Identification of error, classification of error and analyze of error. The result of this research shows that there are 49 total data in the â€œstatusâ€ on Facebook. The 3 kinds of error analysis in the theory of Ellis, which are Omission, Misinformation, and Misordering. This research is expected to be a benefit for everyone especially for those who interested in Applied Linguistics.Â Â Â Keyword : Error Analysis, Status Social Media Facebook.